Two new deep-sea species of Laonice (Annelida: Spionidae) from the Mediterranean Sea - Sikorski, Andrey V.; Pavlova, Lyudmila V.; Sardá, Rafael; Langeneck, Joachim; Gil, João; Ravara, Ascensão (Zootaxa, 2021)
Two new deep-sea species of the genus Laonice belonging to the subgenera Sarsiana and Appelloefia respectively, are described from the Mediterranean Sea. Complete specimens of the subgenus Appelloefia were studied for the first time, and the new information collected raised questions on the boundaries between the subgenera Appelloefia and Norgensia. The presence of characters in L. barcinensis sp. nov. previously considered to be exclusive to each these two subgenera suggests that they should be regarded as synonymous. The name Appelloefia being given precedence here, according to the Principle of the First Reviser. A correction is made regarding the depth range of Laonice rasmusseni Sikorski & Pavlova, 2018.